Conditional resource management for mobile devices - Pérez, Martín (2014)
Mobile devices, such as smartphones and tablets, are becoming more popular everyday. This new devices class is constantly evolving on what concerns computing capabilities, allowing users to switch from larger computers to smaller mobile devices in several cases. Everyday new apps for these devices are developed and published in software repositories, enabling users to quickly install and benefit from new software. In order to deal with the multiple resource requests from different applications running in parallel, the operating system’s resource management design plays a key role. Most resource managers available to mobile phones are designed to maximize the performance of the system as a whole, not always taking into account the characteristics of the processes requiring resources in the application layer. This type of strategy can lead to cases where some applications experience longer latencies than desired while accessing resources, compromising the Quality of Service or system security. This work aims to offer a new resource management model for mobile devices, allowing the creation of rules that can prioritize the resource allocation for specific applications according to their needs. Also it implemented a proof of concept prototype version of this model, using the Android platform, confirming its viability.